PTU-012 The impact of comorbidity on post liver transplant survival and resource utilisation in patients transplanted for acute liver failure utilising the Charlson comorbidity index. (28th May 2012) - Al-Freah, M A B; Kok, B; Bernal, W; Auzinger, G; Heaton, N D; O'Grady, J G; Heneghan, M A; Wendon, J A
Abstract : Introduction: The presence of comorbidities negatively impact post liver transplant (LT) survival for those transplanted with chronic liver disease. Methods: assess the impact of comorbidities on survival in patients transplanted for acute liver failure (ALF). Results: 176 patients underwent LT for ALF over 9 years. Median follow-up was 92 months (range 35–142). Median age was 33 years (17–67) and 122 (69.3%) were females. Fifty-nine patients (33.5%) were transplanted for Paracetamol induced ALF. Ninety-six (54.6%) patients had ≥1 comorbidity. The commonest comorbidity was renal dysfunction in 84 (48%), pulmonary disease in 10 (6%), connective tissue disease in 5 (3%) and 2 (1%) had diabetes. Patients with ≥1 comorbidity had significantly increased 6 month (25% vs 13%, p=0.046), 12 month (27% vs 13%, p=0.023) and overall mortality (32% vs 17%, p=0.019). Similar results were demonstrated for graft survival. Recipient age ≥ 40 years (OR=1.37, 95% CI 1.02 to 1.86, p=0.039), the presence of comorbidity (OR=1.46, 95% CI 1.05 to 2.03, p=0.022) and renal dysfunction (OR=1.62, 95% CI 1.18 to 2.23, p=0.003) were associated with increased post LT mortality on univariate analysis. However, only the presence of comorbidity (OR=1.43, 95% CI 1.03 to 1.98, p=0.032) and renal dysfunction (OR=1.59, 95% CI 1.15 to 2.19, p=0.004) were independently associated with mortality. Other recipient related, donor, or graft variables were not associated with mortality. Patients with ≥1 comorbidity had significantly increased ICU length of stay (LoS) of 20 days (3 to 134) compared to those without comorbidities, 16 days (2–102), p=0.005. Conclusion: Pre- LT comorbidity as defined by the presence of ≥1 comorbidity, significantly impairs overall post-LT patient and graft survival in patients transplanted for ALF. Patients with ≥1 comorbidity had significantly increased ICU LoS which may suggest increased resource utilisation. Competing interests: None declared. Reference: 1. Volk ML, et al . Modified Charlson comorbidity Index for predicting survival after liver transplantation. Liver Transplant 2007;13 :1515–20.